Využití nástrojů projektového managementu v praxi při řízení IT projektů - Čečotková, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce se zabývá využitím metod projektového managementu v praxi, konkrétně při zavádění nového informačního systému v církevní neziskové organizaci. Úvodní část se věnuje teoretickým východiskám práce, které jsou následně využity v návrhovém oddílu. Analytický úsek se zabývá současným řízením projektů organizací a některými analýzami využívanými v předprojektové fázi projektu. Na analytickou část navazuje návrhová část, jenž čerpá z provedených analýz a využitých metod a podává návrh řešení projektového řízení uplatnitelného do budoucna.

The bachelor‘s thesis approaches the use of project management methods in practice, specifically in the implementation of a new information system in a church non-profit organization. The introductory part is devoted to the theoretical basis of the thesis, which are then used in the practical section. The analytical section deals with the current project management of the organization and some of the analyzes used in the pre-project phase of the project. The analytical part is followed by the practical section, which draws on the performed analyzes and used methods and submits a proposal for the solution of project management applicable in the future.
The Use of Methods of the Project Management in Practice in IT Projects
Keywords: projektový management; projekt; informační systém; logický rámec; hierarchická struktura prací; analýza rizik; časová analýza; Ganttův diagram; project management; project; information system; logical framework; work breakdown structure; risk analysis; time analysis; Gantt chart